Single Area Payment - as One of the Supports of Agricultrure in the European Union - Bielik, Peter; Turceková, Natália (Theory, Methodology, Practice – Review of Business and Management, 2007)
The 2003 reform of the CAP introduces a new system of single farm payments (income support) and cuts the link between support and production (decoupling). The majority of common organisations of markets (COMs) will become subject to this new system in 2005 or 2006 (with the exception of the new Member States). Existing direct aids may be continued until 2012, subject to certain conditions (cross-compliance), but they will be gradually reduced (modulation). Certain crops are eligible for additional support to compensate for the loss of income resulting from modulation and the transition to the single farm payment. Council Regulation (EC) No 1782/2003 of 29 September 2003 establishing common rules for direct support schemes under the common agricultural policy and establishing certain support schemes for farmers and amending Regulations (EEC) No 2019/93.